Role of diffuse low-level heteroplasmy of mitochondrial DNA in Alzheimer’s disease neurodegeneration - Casoli, Tiziana; Spazzafumo, Liana; Di Stefano, Giuseppina; Conti, Fiorenzo (Frontiers in Aging Neuroscience, 2015)
Alzheimer’s disease (AD) is the most common form of dementia in the elderly. The vast majority of cases are not linked to a known genetic defect and the molecular mechanisms underlying AD pathogenesis are still elusive. Evidence suggests that mitochondrial dysfunction is a prominent feature of the disease, and that mitochondrial DNA (mtDNA) alterations may represent a possible starting point of the pathophysiological cascade. Although specific mtDNA alterations have been reported in AD patients both in brain and peripheral tissues, such as D-loop mutations, 4977-bp deletion and poly-C tract D310 cytosine insertion, a generalized subtle allelic shift has also been demonstrated. This shift is significant for a few nucleotide positions (nps), but it is also detectable for most nps, although at a lower level. As single allelic substitutions can unlikely be determinant, it is proposed that the combination of all of them could lead to a less efficient oxidative phosphorylation, thus influencing AD development and course.